2013
DOI: 10.3992/jgb.8.4.110
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of Three Different Strawbale Buildings at the Kerkenes Eco-Center

Abstract: By and large, straw is not considered to be a building material, yet in comparison with traditional materials, building with straw bales is definitely more energy-efficient, eco-friendly, and low-cost; qualities that are desirable in sustainable buildings. This paper presents information on three different straw bales buildings at the Kerkenes Eco-Center, which is located in the village of Sahmuratli in central Anatolia, Turkey. The first of these was constructed with load-bearing straw bale walls; the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The construction process itself is very similar to that of masonry, with the installation of alignment guides and alternating positioning of the bales between one layer and the layer above. built in 1903 (3,17,(19)(20)(21), and according to Pritchard and Pitts (12), "the development of strawbale building technology resulted from the colonization of North America by Europeans and the lack of availability of construction materials for building". However, the first European straw bales building was built only in 1921, by Émile Feuillette, in Montargis, France (17,21), indicating that knowledge migrated from America to Europe.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The construction process itself is very similar to that of masonry, with the installation of alignment guides and alternating positioning of the bales between one layer and the layer above. built in 1903 (3,17,(19)(20)(21), and according to Pritchard and Pitts (12), "the development of strawbale building technology resulted from the colonization of North America by Europeans and the lack of availability of construction materials for building". However, the first European straw bales building was built only in 1921, by Émile Feuillette, in Montargis, France (17,21), indicating that knowledge migrated from America to Europe.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, the first European straw bales building was built only in 1921, by Émile Feuillette, in Montargis, France (17,21), indicating that knowledge migrated from America to Europe. These buildings, still in use, were erected more than a century ago and demystify the image of fragility and instability that the mention of straw as a building material can evoke (19).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…THUBERC also reported that the energy consumption in office buildings is approximately 25% of that of the non-domestic building sector in China which is notably higher than ratio for office buildings in the UK and the USA [20]. This is due to the rapid urbanization in China accompanied by a rapid increase in the area of office buildings due to the economic growth.…”
Section: Energy Consumption Of Building Industries In Chinamentioning
confidence: 99%
“…In 2015, the operational energy of buildings exceeded 857 million tons of coal equivalent (TCE) which represents 20% of the total energy consumption in China in that year [1]. Building energy consumption increased by a factor of 1.7 in 2014 from the level in China in 2000 [20] and this energy consumption is estimated to increase further and to reach 35% of the total energy consumption in China by 2020 [21].…”
Section: Energy Consumption Of Building Industries In Chinamentioning
confidence: 99%